MITIGASI BENCANA BERDASARKAN NILAI SHEAR STRAIN TANAH AKIBAT GEMPA BUMI PADA TEMPAT PEMBUANGAN AKHIR (TPA) NGIPIK, GRESIK - Siti Nurlita Fitri; Ria Asih Aryani Soemitro; Dwa Desa Warnana (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
Ngipik Landfill located in Gresik, East Java has a several active fault. As a result, this area has high possibility as an earthquake prone area. In addition, It has not prevent’s layer under the bottom of the construction to control the leachate’s spread. This study aim to analyze the earthquake hazard map for the region based on the values of ground shear strain. The data was conducted by microtremor measurement and Plaxis modeling. The result of this study shows the shear strain value range between 3.5 x 10-3 to 12.5 x 10-3. The highest value is around the east and west-north area and indicated the high risk of damage under ground motion. The output of the research must consider as preliminary site mitigation of Ngipik Landfill.